2018
DOI: 10.29252/ijrm.16.5.335
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiapoptotic effects of the calligonum extract on spermatogonial stem cells

Abstract: Background:Spermatogonial stem cells are the foundation of spermatogenesis and male fertility. So, their maintenance and culture are very important.Objective:In this study, we assessed protective effects of the Calligonum on in vitro viability and apoptotic and antiapoptotic genes expression of spermatogonial stem cells.Materials and Methods:After 24 hr of culture, the spermatogonial stem cells were treated with 30 μM dose of H2O2 and then 10 μg/ml the Calligonum extract was added for 3 wks. Viability was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…On the other hand, the cotreated groups have comparable apoptotic cell numbers to controls and normal spermatids' chromatin. Previous reports revealed that extracts from plants with antioxidant activity can reduce the apoptotic of germ cells caused by chemical toxicity [64,65]. Similarly, pomegranate seed extract prevented germ cell apoptosis, possibly by modulating the ROS/Nrf2/p53 signaling cascade as previously described [66][67][68].…”
Section: Discussionmentioning
confidence: 53%
“…On the other hand, the cotreated groups have comparable apoptotic cell numbers to controls and normal spermatids' chromatin. Previous reports revealed that extracts from plants with antioxidant activity can reduce the apoptotic of germ cells caused by chemical toxicity [64,65]. Similarly, pomegranate seed extract prevented germ cell apoptosis, possibly by modulating the ROS/Nrf2/p53 signaling cascade as previously described [66][67][68].…”
Section: Discussionmentioning
confidence: 53%